2015
DOI: 10.4314/evj.v19i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-intestinal nematodes of sheep and goats in three districts of Kaffa and Bench Maji Zones, Southwest Ethiopia

Abstract: A cross-sectional study was conducted to estimate the prevalence and to identify the genera of gastrointestinal strongyles infecting sheep goats in Chena and Gimbo (Kaffa Zone) and Semen-Bench (Bench Maji zones) districts, Southwest Ethiopia. A total of 800 faecal samples were collected from sheep (n=492) and goats (n=308), and then examined by floatation technique. Positive faecal samples were pooled and cultured and third stage larvae (L 3 ) were harvested and identified. From 800 examined faecal sample 433 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
2
5
0
1
Order By: Relevance
“…As indicated, animals with poor body conditions were more severely infested than animals with medium and good body conditions. This is in agreement with previous scholars’ conclusions from Burie district [ 44 ], Kaffa and Bench Maji zones [ 40 ], Tullu district [ 29 ], and Bedelle [ 45 ]. However, the contradictory conclusion of Dabasa et al [ 33 ] from the Bale zone stated that well-conditioned animals were more prone to GIN infestation than poor and medium-conditioned ones.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As indicated, animals with poor body conditions were more severely infested than animals with medium and good body conditions. This is in agreement with previous scholars’ conclusions from Burie district [ 44 ], Kaffa and Bench Maji zones [ 40 ], Tullu district [ 29 ], and Bedelle [ 45 ]. However, the contradictory conclusion of Dabasa et al [ 33 ] from the Bale zone stated that well-conditioned animals were more prone to GIN infestation than poor and medium-conditioned ones.…”
Section: Discussionsupporting
confidence: 93%
“…The current study found that adult animals had significantly more GIN infestation than young animals.This might be because young kids concentrate on suckling their ewes and does rather than grazing and/or browsing, which could decrease their exposure to infestation. Similar findings were declared in different parts of Ethiopia [ 33 , 40 ], Malaysia [ 47 ], and Lesotho [ 48 ]. However, other researchers from Ethiopia [ 49 ] and abroad [ 50 , 51 ] contrasted with this finding and discovered a higher prevalence of young animals than adults.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Study in eastern part of Ethiopia stated the prevalence of nematodes in sheep and goats with Haemonchus contortus being the most prevalent followed by Trichostrongylus [ 8 ]. Another study in south west Ethiopia reported that 54.1% of sheep and goats were positive for GI parasite eggs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Світова література свідчить, що одна з причин, яка знижує ефективність розвитку вівчарства, -це гельмінтозні захворювання, у тому числі й нематодози травного каналу (Suarez et al, 2009). Широке розповсюдження нематод травного каналу загрожує зростанням чисельності популяції збудників паразитарних захворювань у зовнішньому середовищі та підвищенням ризику зараження тварин й поширенням хвороб на нових територіях (Dhar et al, 1982;Moghaddar, 2008;Kenea et al, 2015).…”
Section: вступunclassified